An in Silico Analysis of Physicochemical Characterization and Protein-Protein Interaction Network Analysis of Human Anti-apoptotic Proteins - VG, Vidhya (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: Apoptosis is a physiological mechanism, playing an essential role in regulating development, homeostasis, and immune defense by removing abnormal cells in organisms. A balance between pro-apoptotic and anti-apoptotic mechanisms determines cell death signal where the pro-apoptotic proteins promote apoptosis and anti-apoptotic proteins inhibit apoptosis. In general, the inhibitors of apoptosis proteins (IAPs) inhibit the caspase activation pathways and play an important roles in regulating apoptosis in many species. Methodology: A total of 50 different human anti-apoptotic proteins retrieved from UniProt Database were analyzed and characterized using in silico tools. A parsimonious phylogenetic tree for these proteins was constructed using the Poisson correction model. Genomic and proteomic data are often combined with protein-protein interaction networks (PPIN) whose structure is routinely analyzed by tools to characterize hubs for treating cancer. Results and Discussion: Primary structure analysis shows that most of the anti-apoptotic proteins are hydrophilic in nature due to the high content of glutamate and serine residues. The presence of disulfide bonding 27 proteins infers that these proteins may form disulfide bonds, which are regarded as a positive factor for stability. The aliphatic index computed by Expasy’s ProtParm infers that these proteins may be stable for a wide range of temperature. Secondary structure analysis shows that most of the human anti-apoptotic proteins have predominant coiled structures due to the rich content of more flexible glycine and proline amino acids. Top 10 hub proteins were identified using PPIN analysis. Conclusion: Thus, the characterization of human anti-apoptotic proteins provides additional targets and new therapeutic approaches for treating cancer.